Pemanfaatan Sawah Warisan Secara Bergilir Menurut Hukum Islam dan Hukum Adat - Endry, Endry; Torik, Muhammad; Purnomo, Bitoh (Muqaranah, 2023)
The use of inherited rice fields in rotation is in accordance with customary inheritance law and article 189 KHI, namely using collective principles. This is not in accordance with the individual principle in Islamic inheritance law. One reason is that in the collective system there is a delay in the distribution of inherited assets. This has the potential to cause conflict. The formulation of the problem in this research is how to implement the use of heritage rice fields in rotation among the Mayapati Village community. The aim of the research is to examine through Islamic law and customary law the rotational use of inherited rice fields in the Mayapati Village community. The type of research is field research with data collection through interviews, observation and documentation. This research is also normative legal research with a qualitative approach, namely data obtained through library materials such as books, documents or statutory regulations related to the problems that occur. Descriptive in nature, that is, the problem is formulated according to the facts that occurred. According to customary law, inherited rice fields are used in rotation according to a collective system. According to the view of Islamic law, inheritance should be divided based on the parts regulated in the text. Referring to the Compilation of Islamic Law, the rotational use of inherited rice fields which is in accordance with Islamic Law is only inherited collectively, in accordance with property rights in Islamic law, namely ownership for the benefit only or haqqul intifa', while the rotational use of rice fields is not in accordance with work regulations. with muzara'ah.